(untitled) (Global Journal of Medical Research, 2023)
This study aimed to evaluate antihyperglycemic and antioxidant activities of an herbal medicinal product codified DD3 From dry aqueous extract the differents tests were carried out Phytochemical screening showed presence of alkaloids polyphenols flavonoids saponosides sterols and terpens Regarding antioxidant activities DPPH test showed that DD3 remedy IC50 59 39 0 69 g mL had a lower antioxidant potential than vitamin C IC50 7 93 0 45 g mL and that was identical for ABTS test for which IC50 94 34 0 73 g mL for the Remedy against IC50 25 87 0 46 g mL for Gallic acid About antihyperglycaemic test unlike glibenclamide which induced hypoglycaemia after 3 hours the remedy at 500 mg kg bw brings blood sugar levels back to normal values after this time The DD3 remedy could be used as a blood sugar regulator